Análisis del uso de las tecnologías de la información y comunicación (TIC) en la formación académica de los estudiantes de sexto ciclo de la carrera de comunicación de la UNL periodo de estudio: octubre 2021 – febrero 2022. - Ramos Becerra, Yuliana Bremilda (2023)
Information and communication technologies have taken a great importance in the life of the human being, since several daily activities performed daily in the educational field by teachers and students are developed on internet platforms, which is characterized by digitization and interactivity, which is why communication migrated to virtual spaces of social convergence. Through this research we intend to analyze the use of information and communication technologies in the academic training of students in the 6th cycle of the Communication career at the National University of Loja, study period October 2021 - February 2022. The methodology used for this research is a mixed approach with quantitative and qualitative predominance, through surveys applied to 6th cycle students of the communication career and semi-structured interviews with teachers who teach them. The results indicate that ICTs are indispensable tools in the teaching-learning process, since they provide a number of benefits and make classes more interactive and didactic, allowing to maintain a harmonious and non-routine environment between students and teachers. The analysis of information and communication technologies leads us to keep in constant training on the use of ICT in the teaching-learning process and thus to discover new things thanks to the daily innovation process of technological tools Keywords: TIC, information technology, use of technologies, academic blackground.